Optimalisasi penggunaan POC limbah cair tahu terhadap produksi tanaman sawi putih (Brassica pekinensis L.) - Indah Trifebriana; Nofrianil; Silfia (Fakultas Pertanian Universitas Majalengka, 2026)
Chinese cabbage is one of the vegetable commodities with high market demand and relatively stable selling prices at the farmer level in traditional markets. Farmers’ dependence on inorganic fertilisers in cultivation practices has led to declining environmental quality, reduced soil fertility, and increased production costs. In an effort to reduce the use of inorganic fertilisers, environmentally friendly technological innovations have been developed, one of which is the utilisation of tofu industrial wastewater as an eco-friendly fertiliser. Tofu wastewater is often discarded into the environment and has not been utilised optimally. This study aimed to determine the effect of liquid organic fertiliser (LOF) made from tofu wastewater on the growth and production of Chinese cabbage. The study used a one-factor Randomised Block Design (RBD) with five treatment levels and five replications, using doses of 20 ml, 40 ml, 80 ml, and 160 ml each diluted with water. Data were analysed using One-Way ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a significance level of 0.05. The increase in tofu wastewater LOF dosage was in line with the improvement in growth and production of Chinese cabbage, comparable to plants treated with 100% NPK fertiliser. The optimal growth and production were obtained at the 160 ml dosage, which was able to replace the use of 100% NPK fertiliser.